철강산업의 온실가스 배출 탈동조화 국제비교 - 김동구; Dong Koo Kim (자원·환경경제연구, 2022)
철강산업은 온실가스 배출량이 가장 많은 제조업이면서 핵심소재산업으로서 국민경제에 미치는 파급효과가 크다. 본 연구는 한국, 일본, 독일을 중심으로 1990~2019년 기간에 걸쳐 철강산업의 온실가스 배출 탈동조화 양상을 국제비교하였다. 특히, 연료연소 배출량만을 고려한 선행연구들과는 달리 본 연구에서는 연료연소 배출량, 산업공정 배출량, 전력 및 열 사용에 따른 간접 배출량을 모두 고려하였다. 분석결과, 한국은 확장적 동조화, 일본은 탈동조화, 독일은 불분명으로 해석된다. 따라서 한국 철강업이 나아가야 할 탈동조화 경로는 독일이 아니라, 일본과 유사하거나 일본보다 더 효과적인 탈동조화 방안을 모색하는 형태로 진행되어야 할 것이다. 또한, 본 연구는 철강업의 특성을 최대한 고려하고 일본 및 독일과의 비교를 통해 탈동조화 분석결과의 원인과 한국 철강업에의 시사점도 제시하였다. 특히, 일본의 탈동조화 촉진 요인으로 일본 철강재의 고부가가치화, 일본 철강산업의 에너지효율기술 개발, 일본 철강산업의 전략적 M&A, 일본 철강재의 폐쇄적 유통구조에 따른 경쟁력 유지, 4가지를 제시하였다. 한국 철강업도 일본의 사례를 벤치마크로 삼아 철강재의 품질 고도화 및 품목 다변화를 통해 부가가치를 더 높이는 동시에, 신기술 개발을 통해 온실가스를 근본적으로 줄이기 위해 노력해야 할 것이다. The iron and steel industry is a manufacturing industry with the largest greenhouse gases emissions and has a great ripple effect on the national economy as a core material industry. This study internationally compared the decoupling patterns of greenhouse gases emissions in the iron and steel industry from 1990 to 2019, focusing on Korea, Japan, and Germany. In particular, unlike previous studies that considered only fuel combustion emissions, this study considered all fuel combustion emissions, industrial process emissions, and indirect emissions from the use of electricity and heat. As a result of the analysis, Korea is interpreted as expansive coupling, Japan as decoupling, and Germany as unclear. Therefore, the decoupling path that the Korean iron and steel industry should take should not be in Germany, but in the form of seeking a decoupling method similar to Japan or more effective than Japan. In addition, this study considered the characteristics of the iron and steel industry as much as possible and presented the causes of the decoupling analysis results and implications for the Korean iron and steel industry through comparison with Japan and Germany. In particular, four factors were suggested as factors which has promoted decoupling in Japan: high value-added of Japanese iron and steel products, development of energy efficiency technology in the Japanese iron and steel industry, strategic M&A of the Japanese iron and steel industry, and maintaining competitiveness according to the closed distribution structure of Japanese iron and steel products. The Korean iron and steel industry should also use the case of Japan as a benchmark to further increase added value through quality uprade and product diversification of iron and steel products, while at the same time making efforts to fundamentally reduce greenhouse gas emissions through the development of new technologies.